ANALISIS LAPORAN REALISASI ANGGARAN PENDAPATAN DAN BELANJA DAERAH UNTUK MENILAI KINERJA PEMERINTAH - Basni, Umar; Ngumar, Sutjipto (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is meant to find out how the preparation of budget and what sort of barriers that are encounteredby the Surabaya city government in the preparation of budget. This research is qualitative research approach.The analysisis the local financial performance analysis which is carried out by there venue variance analysis, thedegree of the decentralization, the local financial dependency ratios, analysis of variance expenditure, theexpenditure efficiency ratio, and financing analysis. In this research, the significant barriers in all existingemployment programs at the Revenue Offices of Surabaya city have not been found yet. Based on the result ofthe calculation and the analysis of the local financial performance, it can be concluded that the difference inbudget revenue has negative balance, it indicates that revenue performance is quite well although it cannot earnincome which is compatible with the budgeted amount. The regional financial dependency ratio indicates that theSurabaya city government in carrying out its activities does not rely on the central government/province. Theanalysis of variance shows that difference of expenditure budget has negative balance which indicates that thereis an efficiency or budget savings. The financing analysis shows that the SILPA has negative balances theSurabaya city government is appropriate in preparing budget plan or in other words the realization of SILPAdoes not exceed from what that has already been set in the budget.Keywords : Local government budget, financial performance, effectiveness, efficiency